Neutron radiation induced transmutation of boron to lithium in aluminum-boron nitride composite - Sohail M.A.K. Mohammed; Zehao Li; Kazue Orikasa; Arun Devaraj; David Garcia; R. Sarvesha; Anil Lama; Mayur Pole; Cheol Park; Sang-Hyon Chu; Ken Ross; Arvind Agarwal (Materials Today Advances)
Lightweight materials are essential for applications in harsh environments, such as space explorations, where materials must exhibit exceptional durability and resistance to radiation damage for both humans and equipment. Boron nitride nanoplatelets (BNNPs) serve as a reinforcement in metals offering superior radiation shielding along with excellent thermal and mechanical properties for extreme environments. In this work fully dense Al-BNNP composites are fabricated by solid-state friction stir welding (FSW). The neutron mass absorption coefficient of the FSW Al-BNNP composite was measured at 0.136 cm2/g, significantly higher than the 0.06 cm2/g of its counterpart FSW aluminum. This remarkable neutron shielding effectiveness is attributed to the transmutation of the 10B isotope of BNNP to Li and He. This neutron capture mechanism was experimentally investigated at the atomic scale by atom probe tomography (APT). Notably, Al-BNNP composites demonstrate great potential as multi-functional materials for future space explorations, from spacecraft assemblies to rocket fuel tanks, benefiting from their high strength, low weight, and superior radiation shielding.